Organização Não Governamental (ONG) : conhecendo suas possibilidades e desafios na atuação da Educação Especial - Zanollo, Luciano José Marchiori (Universidade Federal de São Carlos, 2009)
The aim of this study was to determine the ways necessary for the establishment and maintenance of a Non-Governmental Organization (NGO) and present some possibilities of action in Special Education. In the city of São Carlos, directors of NGOs working in Special Education were interviewed, to ascertain why this NGO was founded, what its goals were, its difficulties, how its role is and what organs it is linked to, what society segments and partners and its actions are, besides informing its difficulties and challenges. The participants were five directors of NGOs working with Special Education. The interviews took place by appointment and were recorded on a digital video recorder and later transcribed in full. For support and discussion of the interviews it was raised the theoretical reference by getting information on legal aspects, which must be considered for the establishment and maintenance of an NGO, as well as some means to manage and execute a project. The contemporary vocation of an NGO is to mobilize people and to propose actions and partnerships between the Public and Private sectors. It was observed in these interviews that the NGOs had in their responses similar expressions and this allowed a reflection on the theme NGOs, Special Education and its possibilities and challenges.
NGOs: knowing the third sector and its possibilities and challenges in the performance of Special Education
Keywords: Educação especial; Organizações não-governamentais; Deficiência; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL